Islamic Theology at Western European Universities : Articulating Ikhtilāf in the Netherlands, Germany, United Kingdom and Austria - Boender, Welmoet, (Middle East and Islamic Studies E-Books Online, Collection 2026, 2026)
In recent years, several Western European universities have started academic programs in Islamic theology. This study answers a much-debated question: How do Islamic theologians at Western European universities face the challenging task of administering, elaborating and developing Islamic knowledge through academic discourse? This book systematically shows how scholars, first and foremost, want to use the academic space to mobilise a paradigm shift that focuses on plurality and pluralism. This approach is aimed at allowing European Muslims comfort and certainty to deal with the challenges of modern life. The study will explain this by using the concept of ikhtilāf , an Islamic legal term, which, at its broadest, can be defined as the recognition of diversity in opinions.